Analysis Of Maximum Braking Force Disc Brake And Drum Brake On Toyota Avanza G 1.3 M/T - MAKRUF, AMAR (2011)
Brakes are a vital part of the vehicle, which serves to slow or stop the vehicle. There are various types of brakes that have the characteristics of each. Author of this final goal is to assess vehicle brake problems Toyota Avanza G 1.3 M / T. the use of disc brakes (ventilated disc) on the front wheel and brake drum (leading-tailing) on the rear wheels. The objective to determine the maximum braking capacity of the front axle and rear axle with the vehicle speed difference. Analysis done by changing the speed of the vehicle speed but with the same stopping distance which one the variation of speed 50 km/h, 55 km/h, 60 km/h, 80 km/h, 100 km/h and the stopping distance is 50 meter. From the calculation of the dynamics of vehicle braking, it was found that Toyota Avanza vehicles at speeds 100 km/h the deceleration is 7.743 m/s2 provide braking force is 10,457.379N on the front axle and the braking force is 5,211.024N on the rear axle, at speeds 80 km/h the deceleration is 4.928 m/s2 provide braking force is 9,636.898N on the front axle and the braking force is 4,505.004N on the rear axle. at speeds 60 km/h the deceleration is 2.751 m/s2 provide braking force is 9,002.444N on the front axle and the braking force is 3,866.09N on the rear axle. at speeds 55 km/h the deceleration is 2.310 m/s2 provide braking force is 8,873.968N on the front axle and the braking force is 3,682.31N on the rear axle, at speeds 50 km/h the deceleration is 1.904 m/s2 provide braking force is 8,755.632N on the front axle and the braking force is 3,553.834N on the rear axle. Braking force is a vehicle braking force needs to be met by the brake unit contained in vehicle.